Eurostat regional yearbook 2018 edition. Statistical Books (Luxembourg, 2018)
"Statistical information is an important tool for understanding and quantifying the impact of political decisions in a specific territory or region. The Eurostat regional yearbook 2018 gives a detailed picture relating to a broad range of statistical topics across the regions of the EU Member States, as well as the regions of the EFTA and candidate countries. Each chapter presents statistical information in maps, tables, figures and infographics, accompanied by a descriptive analysis highlighting the main findings. Regional indicators are presented for the following 12 subjects: regional policies and European Commission priorities, population, health, education and training, the labour market, the economy, structural business statistics, research and innovation, the digital economy and society, tourism, transport, and agriculture. In addition, two special chapters are included in this edition: a focus on European cities and a focus on regional typologies."